Bible Study Scheduling Information System Using Rapid Application Development Method in GKS Jemaat Padadita Barat - Willem, Maria Adreana Elisabeth; Murry Albert. A. Lobo; Pingky Alfa Ray Leo Lede (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Along with technological developments in the field of information systems, great opportunities arise to improve the efficiency and performance of various institutions, including churches. The church as an institution that has an important responsibility in serving the congregation, requires an effective information system to support various service activities. One example is GKS Jemaat Padadita Barat, which currently manages the Bible Study (PA) schedule using traditional methods. The PA schedule management is done by an officer, namely the secretary, by typing the schedule using Microsoft Word and printing it manually. This method is not only time-consuming but also inefficient and prone to errors.To answer these challenges, a website-based information system is needed that can help manage PA schedules more efficiently and integrated. This research aims to design and build a website-based PA scheduling information system specifically designed to assist congregational assemblies in managing congregational data and preparing PA schedules. This system is expected to facilitate access, speed up data management, and allow real-time schedule updates.This research uses the Rapid Application Development (RAD) method, which is well-known for its ability to produce systems quickly, structurally, and efficiently. The implementation of this system is expected to optimize the management of PA schedules at GKS Jemaat Padadita Barat, support church services, and increase congregational satisfaction in participating in PA activities.